2015
DOI: 10.1002/ijop.12203
|View full text |Cite
|
Sign up to set email alerts
|

Publication patterns in developmental psychology: Trends and social networks

Abstract: Interest in publication patterns has been steady. Journals have instituted policies in an effort to curb bias and provide globally representative research. This study aimed to examine if publication patterns were present in two developmental psychology journals. It also explored the social networks of prominent authors and the prevalence of informal author-editor relationships, searching for any potential power groups. Data were taken from empirical articles published between 2005 and 2014 in Child Development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…A third limitation is our focus on only English-language literature, which necessarily excludes papers written in Russian and French, and, as such, may contribute to the geographic distribution of studies noted above. We note that language barriers have been a challenge for collaboration in Arctic studies, and this can reinforce the issue of invisible colleges discussed below (Dobermann and Hamilton 2017). Cross-cultural collaboration in Arctic research that addresses the language barrier would be extremely valuable.…”
Section: Limitationsmentioning
confidence: 84%
See 2 more Smart Citations
“…A third limitation is our focus on only English-language literature, which necessarily excludes papers written in Russian and French, and, as such, may contribute to the geographic distribution of studies noted above. We note that language barriers have been a challenge for collaboration in Arctic studies, and this can reinforce the issue of invisible colleges discussed below (Dobermann and Hamilton 2017). Cross-cultural collaboration in Arctic research that addresses the language barrier would be extremely valuable.…”
Section: Limitationsmentioning
confidence: 84%
“…It is essential that researchers be self-aware of the possible influence that these networks, regardless of how they form, can have on how knowledge is generated: invisible colleges can have a sizable impact on accepted methodology and scholastic achievements in an area of research, as they inflate citations of college members relative to non-college members, and in so doing influence research patterns, for example, acceptable methodologies and analytical frameworks. In psychological research, for example, invisible colleges have been shown to keep new researchers out of established fields of specialization, because of "in-group favoritism" and by amplifying linguistic and cultural barriers (Dobermann and Hamilton 2017). We likewise know from Indigenous scholarship that invisible colleges can create a "politics of citation" that perpetuate structural inequities in academia that limit the inclusion of marginalized voices (Todd 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of this study was based on the concepts of text mining and NLP. For more, please refer to [5][6][7][14][15][16]18,[27][28][29][30]. In the SCI (science citation index) and SSCI (social science citation index) articles of [31], through the steps of text retrieval, word segmentation, word cloud analysis, TF-IDF analysis, co-word analysis, network analysis, trend analysis, etc., the text data of the two regions are excavated for comparison and analysis of their similarities and differences.…”
Section: Methodsmentioning
confidence: 99%
“…In order to make up for the shortcomings of the content analysis method, such as being time-consuming, laborious, and not objective, this study proposes a program for analyzing and processing text data in sports-related fields based on the concept of NLP, which is different from the traditional content analysis method, with a faster automative analytical process and the ability to systematically extract and analyze the importance and relevance of keywords in abstract content [5,13]. It integrates the methods of word segmentation, word cloud analysis, TF-IDF (term frequency-inverse document frequency) analysis, and co-word analysis, and then applies visual network diagramics drawing technology [14][15][16][17][18] to present the distribution of core keywords and their network relationships in sports research abstracts from China and Taiwan (a total of 3,283 articles). This reveals possible hidden knowledge structures and provides an important reference for evaluating future development trends in the two regions.…”
Section: Introductionmentioning
confidence: 99%